Alternatif Penyelesaian Sengketa Secara Arbitrase Melalui Pemanfaatan Teknologi Informasi - Faisal Riza; Rachmad Abduh (Universitas Muhammadiyah Sumatera Utara, 2019)
Dispute resolution in essence can be done through two processes, namely the litigation process in court and non-litigation outside the court. In general, the litigation process will produce adversial agreements that have not been able to embrace common interests because their interests are facing each other. The results of the dispute resolution process in the courts tend to cause new problems, spend a long time, require expensive, unresponsive, and cause hostility between the parties to the dispute. Through a dispute resolution process outside the court, it will result in a win-win agreement solution, guaranteed confidentiality, protected from slow administrative procedures, low costs, good relations will still be established for the parties to the dispute. Arbitration is a way to resolve civil disputes outside the general court. The method of settlement is based on an arbitration agreement made in writing by the parties to the dispute. The main prerequisite for an arbitration process is the obligation of the parties to the dispute to make a written agreement (arbitration clause), and then agree on the law and procedure for how they will end the dispute. Arbitration settlement is widely used in trade disputes. The increasing development of trade, finance and national and international industries in the current era of globalization has led to advances in the economy and industry.